Developing A Framework for Accident Detecting and Sending Alert Message Using Android Application - Shukran, Mohd Afizi Mohd; Abdullah, Muhammad Naim; Isa, Mohd Rizal Mohd; Ismail, Mohd Nazri; Khairuddin, Mohammad Adib; Maskat, Kamaruzaman (International Journal of Engineering and Technology, 2018)
Accident detection systems help reduce fatalities stemming from car accidents by decreasing the response time of emergency responders. This paper focuses on development a framework for detecting accident and sending alert message using android application. The proposed framework developed in order to produce the android application or system with three main functional components which are detecting the occurrence of the crash, detecting the location of the crash and sending the alert message. These three components are interdependent on each other by the flow of the system.